Commercial Ventures in Nonprofit Organizations: Strategic Change or Natural Evolution? - Meinhard, Agnes; Foster, Mary; Moher, Louise; FitzRandolph, Susan (The Hungarian Journal of Marketing and Management, 2019)
This paper investigates the change processes involved in establishing commercial ventures as revenue generating alternatives in eleven nonprofit organizations, and reports on factors contributing to their success. The eleven cases studied illustrate that the establishment of commercial ventures in nonprofit organizations may result from either deliberate planning or following emergent opportunities. Regardless of whether change was emergent or deliberate, successful organizations were ones that did not try to radically change their paradigms. Their ventures were either merely an extension of existing physical or human resources, or entwined with their mission very early in their life cycle. The unsuccessful and struggling ventures, however, were the result of intended, deliberately planned change strategies that failed because the ventures failed to mesh with the organization’s paradigm.